Direct detection of fibrinogen in human plasma using electric-double-layer gated AlGaN/GaN high electron mobility transistors - Regmi, Abiral; Sarangadharan, Indu; Chen, Yen-Wen; Hsu, Chen-Pin; Lee, Geng-Yen; Chyi, Jen-Inn; Shiesh, Shu-Chu; Lee, Gwo-Bin; Wang, Yu-Lin (Applied physics letters, 2017)
Fibrinogen found in blood plasma is an important protein biomarker for potentially fatal diseases such as cardiovascular diseases. This study focuses on the development of an assay to detect plasmatic fibrinogen using electrical double layer gated AlGaN/GaN high electron mobility transistor biosensors without complex sample pre-treatment methods used in the traditional assays. The test results in buffer solution and clinical plasma samples show high sensitivity, specificity, and dynamic range. The sensor exhibits an ultra-low detection limit of 0.5 g/l and a detection range of 0.5–4.5 g/l in 1× PBS with 1% BSA. The concentration dependent sensor signal in human serum samples demonstrates the specificity to fibrinogen in a highly dense matrix of background proteins. The sensor does not require complicated automation, and quantitative results are obtained in 5 min with <5 μl sample volume. This sensing technique is ideal for speedy blood based diagnostics such as POC (point of care) tests, homecare tests, or personalized healthcare.